2020
DOI: 10.1016/j.injury.2020.02.070
|View full text |Cite
|
Sign up to set email alerts
|

Early efficacy evaluation of mesenchymal stromal cells (MSC) combined to biomaterials to treat long bone non-unions

Abstract: Background and study aim: Advanced therapy medicinal products (ATMP) frequently lack of clinical data on efficacy to substantiate a future clinical use. This study aims to evaluate the efficacy to heal long bone delayed unions and non-unions, as secondary objective of the EudraCT 2011-005441-13 clinical trial, through clinical and radiological bone consolidation at 3, 6 and 12 months of follow-up, with subgroup analysis of affected bone, gender, tobacco use, and time since the original fracture. Patients and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 32 publications
0
61
0
Order By: Relevance
“…Thus, a more logical option for regeneration of bone is to revert to an earlier stage in the lineage, such as the pre-osteoblast or the MSC. In preclinical studies, and in limited clinical trials (Gomez-Barrena et al, 2015 , 2020 ; Lee et al, 2019 ; Hutchings et al, 2020 ), MSCs have been the target cell for isolation. As outlined above, MSCs are rare in the bone marrow; the approach most commonly used is expansion in vitro , and then injection or open grafting in a suitable carrier.…”
Section: Methods Of Cell Expansion and Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a more logical option for regeneration of bone is to revert to an earlier stage in the lineage, such as the pre-osteoblast or the MSC. In preclinical studies, and in limited clinical trials (Gomez-Barrena et al, 2015 , 2020 ; Lee et al, 2019 ; Hutchings et al, 2020 ), MSCs have been the target cell for isolation. As outlined above, MSCs are rare in the bone marrow; the approach most commonly used is expansion in vitro , and then injection or open grafting in a suitable carrier.…”
Section: Methods Of Cell Expansion and Selectionmentioning
confidence: 99%
“…Given the above controversy, there have been many different methods for isolation of what the authors describe as mesenchymal stem cells (Kanczler et al, 2019 ) ( Figure 1 ). One such methodology for GMP compliant generation of bone marrow derived MSCs and expansion on a large scale for a multicenter study of fracture healing in Europe has been described in detail (Fekete et al, 2012 ; Rojewski et al, 2013 ; Gomez-Barrena et al, 2020 ). This and other studies using MSCs are ongoing.…”
Section: Methods Of Cell Expansion and Selectionmentioning
confidence: 99%
“…A recent article showed that bone healing was efficaciously achieved in 28 patients with nonunions surgically treated with a combination of autologous expanded mesenchymal stromal cells from human bone marrow (hBM-MSCs) (between 100 × 10 6 and 200 × 10 6 expanded hBM-MSCs) combined with a bioceramic [MBCP + TM, a 100% synthetic (Biomatlante, Vigneux, France) bone substitute composed of 20% hydroxyapatite and 80% beta-tricalcium phosphate, in 1–2 mm granules]. The cell-biomaterial association was performed in the surgical room prior to implantation [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…An aliquot of the starting material was removed to carry out controls, including cell count, viability, CFU-F-assay, and sterility. The entire manufacturing process was performed at each manufacturing site, following the same procedure described in ORTHO-1 CT (EudraCT 2011-005441-13) and ORTHOUNION CT (EudraCT 2015-000431-32) [ 14 , 15 ]. In brief, the culture was performed when the received BM, without any further manipulation, was seeded in alpha-MEM medium with 5% PL and 1 I.U./mL heparin, at the concentration of 50.000 WBC/cm 2 , in a culture chamber.…”
Section: Methodsmentioning
confidence: 99%